The influence of the NHT type cooperative learning model on the accuracy process of passing - Prasetyo, Rama; Hadiana, Oman; Nur, Hana Astria; Heriyana, Tio; Hermawan, Hermawan (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Abstract: This research aims to determine the influence of the NHT-type cooperative learning model on the process of upper passing accuracy of volleyball for students of Mattayom 6 Vuttisatvittayanusorn School Krabi. This research applied Classroom Action Research (CAR), which consisted of three cycles. Each cycle covered three meetings. The subjects of this research were 20 students in class Mattayom 6 Vuttisatvittayanusorn School Krabi. The instruments used in this study were the upper passing assessment sheet and observation sheet for students. The observation results indicate that upper passing learnings through the NHT Mattayom 6 Vuttisatvittayanusorn School Krabi type cooperative learning model for three cycles influence the process of upper passing accuracy. This is manifested in the learning observations of 20 students. In cycle I, four students achieved a higher score of minimum learning mastery standard (KKM 70). In cycle II, it increased to 8 students. Then, in cycle III, it increased to 17 students who achieved the score of minimum learning mastery standard (KKM) 70. Thus, more than 85% of students have completed classical completion in this class. Keywords: Cooperative Learning Model, NHT type, upper passing accuracy of volleyball